Kesadaran Multikultural dan Deradikalisasi Pendidikan Islam: Pengalaman Bhinneka Tunggal Ika dan Qabul Al-akhar - Misrawi, Zuhairi (Jurnal Pendidikan Islam, 2013)
In Indonesia, plurality of historical religion, ethnic, culture, and language made national consciousness in the historical course up to now. This phenomenon made public disappointed, especially regarding to the rise of intolerance, and violence. This article is about the importance of multiculturalism as an alternative to develop peacefully life awareness and togetherness in the context of national and universal humanity. In this case, the multiculturalism necessitates coexistence, openness, recognition, understanding, acknowledgement, and appreciation. The comparison between Indonesia and Egypt in building multicultural awareness, especially through the philosophy of unity in diversity and Qabul al-Akhar.